A highly fragrant comestible: the cartilaginous fish (Chondrichthyes) in pre‐European Māori New Zealand. Issue 1 (5th October 2021) - Campbell, Matthew; Shepherd, Lara; Kellett, Melissa; Brassey, Robert
ABSTRACT: A count of 6235 Chondrichthyes vertebrae was recovered from the 17th to 18th century AD NRD site (R11/859) on the Manukau Harbour, Auckland, New Zealand. These have been identified by aDNA analysis as mostly rig ( Mustelus lenticulatus ). To provide context for this unusual assemblage we briefly review the archaeological record of Chondrichthyes fishing in Oceania and New Zealand, and more extensively review the 19th and early 20th century ethnography of Māori shark fishing in New Zealand along with the archaeological record. Chondrichthyes were of economic, social and spiritual importance to pre‐European Māori. A variety of species were caught by a variety of techniques, including mass harvest, and could be dried for storage. Our initial reading of the ethnographic record led us to expect that the assemblage would be dominated by school shark ( Galeorhinus galeus ), but a closer analysis of the record showed that Māori sharking practice was diverse. The NRD assemblage encapsulates this variation. RÉSUMÉ: Un nombre de 6235 vertèbres de Chondrichthyes a été collecté sur le site NRD (R11/859) dans l'estuaire de Manukau datant du 17ème‐18ème siècle, Auckland, Nouvelle‐Zélande. L'analyse de ces vertèbres par ADNa permis d'identifier ces échantillons comme étant principalement des rig ( Mustelus lenticulatus ). Afin de fournir un contexte pour cet assemblage inhabituel, nous passons brièvement en revue les archives archéologiques de la pêche aux Chondrichtyens en Océanie et en Nouvelle‐Zélande, et nous examinons plus en détail l'ethnographie du 19ème et du début du 20ème siècle de la pêche au requin par les Māori en Nouvelle‐Zélande ainsi que les archives archéologiques. Les Chondrichtyens avaient une importance économique, sociale et spirituelle pour les Māori pré‐européens. Une variété d'espèces étaient capturées par diverses techniques, y compris la récolte intensive, et pouvaient être séchées pour être stockées. Notre lecture initiale du dossier ethnographique nous a amené à penser que l'assemblage serait dominé par le requin école ( Galeorhinus galeus ), mais une analyse plus approfondie du dossier a montré que la pratique du requin par les Māori était diverse. L'assemblage de la NRD reflète cette variation.